PERANAN KELOMPOK PETERNAK DALAM MENUNJANG KEBERHASILAN USAHA SAPI POTONG DI KABUPATEN BOALEMO - Hasnawati, Hasnawati; Fariyanti, Anna; Mulatsih, Sri (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2014)
ABSTRACTThis research was carried out in Wonosari District, Boalemo Regency, Gorontalo Province on April – July 2014. This research aimed : (1) to analyze the factors influencing the earnings of the cattle breeders in Boalemo Regency, (2) to analyze the performance of the cattle breeders towards the success of beef cattle business in Boalemo Regency, (3) to formulate the strategy to increase the cattle breeders’ role in supporting the business of beef cattle in Boalemo Regency. This research used the method of purposive sampling, and the criteria of breeders used were group of cattle breeders and non-group of cattle breeders (independent cattle breeders). The number of sample used in the survey was 30 members of cattle breeder group and 20 respondents from non-group of cattle breeders. The analysis instruments used were (1) the analysis of beef cattle business, (2) the analysis of Multiple Linear Regression, (3) the Importance Performance Analysis (IPA).The analysis result of the earning in 3,76 AU (animal unit) scale was Rp 3.010.849 year and non-group in 3,48 AU scale was Rp 3.983.934 year. The factor influencing farmer income are the number of bull, number of cow, and forage consumtion. The result of Importance Performance Analysis showed that the atribute in the first quadrant had the high level of importantance, but low performance, i.e. (1) getting the additional feed/beef cattle business consentrate, (2) the skill of group member, (3) the facility of means and infrastructure supporting the animal husbandary, (4) obtaining the financial for beef cattle business, and (5) the organization establishment of beef cattle group members.Key words: group role, double linear regression, importance performance analysis, policy strategy, Boalemo regency ABSTRAKPenelitian dilaksanakan di Kecamatan Wonosari Kabupaten Boalemo Provinsi Gorontalo pada bulan April sampai Juli 2014. Penelitian ini bertujuan : (1) Menganalisis faktor-faktor yang mempengaruhi pendapatan kelompok peternak sapi potong di Kabupaten Boalemo, (2) Menganalisis kinerja kelompok peternak terhadap keberhasilan usaha sapi potong di Kabupaten Boalemo, (3) Merumuskan strategi untuk meningkatkan peran kelompok peternak dalam menunjang usaha sapi potong di Kabupaten Boalemo. Pengambilan sampel secara purposive sampling,sampel dalam survey terdiri dari 30 anggota kelompok peternak dan 20 peternak non anggota kelompok. Alat analisis yang digunakan yaitu; (1) Analisis pendapatan usaha ternak, (2) Analisis Regresi Linier Berganda, (3) Importance Performance Analysis (IPA). Pendapatan usaha pembibitan sapi potong pada kelompok peternak skala 3,76 ST sebesar Rp 3.010.849 /tahun dan peternak non kelompok skala 3,48 ST sebesar Rp 3.983.934 /tahun. Factor yang mempengaruhi pendapatan peternak adalah jumlah pejantan dan induk sapi yang dimiliki serta pemberian pakan hijauan. Hasil Importance Performance Analysis menujukan bahwa atribut yang berada pada kuadran pertama memiliki tingkat kepentingan yang tinggi namun kinerjanya masih rendah, yaitu (1) memperoleh pakan konsentrat, (2) Keterampilan anggota kelompok, (3) Fasilitas sarana dan prasarana pendukung peternakan, (4) Memperoleh modal usaha beternak sapi potong, dan (5) Pembinaan Kelembagaan Peternak Sapi Potong.Kata Kunci: Peranan Kelompok, Regresi Linier Berganda, Importance Performance Analysis, Strategi Kebijakan, Kabupaten Boalemo